تحليل الأخطاء الإملائية في الهمزة لدى طلاب معهد اللغويات العربية بجامعة الملك سعود - Abdelaziz Haroun Abdoulaye (Nady Al-Adab : Jurnal Bahasa Arab, 2020)
الملخص    استهدف هذا البحث على معرفة الأخطاء الإملائية في الهمزة لدى طلاب معهد اللغويات العربية بجامعة الملك سعود، وقد تكونت عينة الدراسة من (23) طالباً ممثلة في ثلاثة مستويات: (المبتدئ والمتوسط والمتقدم)، وقد اعتمدت الدراسة على منهج البحث الوصفي التحليلي، واستخدم الاختبار أداة لجمع المعلومات من عينة الدراسة، وتم التحقق من صدق الأداة وثباتها من خلال عرضها على مجموعة من المحكمين ذوي الاختصاص في المجال، وأشارت نتائج الدراسة إلى وجود فروق ذات دلالة إحصائية بين المستويات الثلاثة، حيث بلغت  نسبة  أخطاء طلاب المستوى المبتدئ في كتابة الهمزة في أول الكلمة (37%)، ونسبة الأخطاء في كتابة الهمزة في وسط الكلمة وصلت إلى (55%)، ونسبة الأخطاء في كتابة الهمزة في آخرة الكلمة (08%). وأما نسبة أخطاء طلاب المستوى المتوسط في كتابة الهمزة المتطرفة فقد بلغت (25.4%)، وبلغت نسبة أخطائهم في كتابة الهمزة في وسط الكلمة (57.3%)، ونسبة الأخطاء في كتابة الهمزة المتطرفة وصلت إلى (17.3%). وبالنسبة لطلاب المستوى المتقدم، فقد بلغت نسبة أخطائهم في كتابة الهمزة في أول الكلمة (33.3%)، ونسبة الأخطاء في كتابتها في وسط الكلمة (60%)، والأخطاء المتعلقة بكتابة الهمزة في آخر الكلمة قد بلغت نسبتها (06.7%)، ونتيجة لذلك فقد خلصت الدراسة إلى مجموعة من التوصيات في ضوء ما أظهرت عنه من نتائج.الكلمات المفتاحية: تحليل الأخطاء ـــ الأخطاء الإملائية ـــ طلاب معهد اللغويات العربية.                    Abstract:   This study aimed to know the spelling errors in Hamza among students of the Institute of Arabic Linguistics at King Saud University. The sample of the study consisted of (23) students represented in three levels: (beginner, intermediate and advanced) .The study relied on the descriptive analytical research methodology.  To collect information from the study sample, the validity and reliability of the tool was verified by presenting it to a group of arbitrators with competence in the field. The results of the study indicated that there are statistically significant differences between the three levels.  (37%), and  The percentage of errors in writing Hamza in the middle of the word reached (55%), and the percentage of errors in writing Hamza in the back of the word (08%).  As for the percentage of mistakes of middle level students in the writing of extreme Hamza (25.4%), and the percentage of mistakes in writing Hamza in the center of the word (57.3%), and the percentage of errors in the writing of extreme Hamza reached (17.3%).  As for the advanced level students, the percentage  of their mistakes in writing the Hamza at the beginning of the word (33.3%), and the percentage of errors in writing in the middle of the word (60%), and errors related to the writing of the Hamza at the end of the word (06.7%), as a result  The study concluded with a set of recommendations in the light of the results shown. Keywords: error analysis - spelling errors - students of the Institute of Arabic Linguistic